PELAKSANAAN PENGELOLAAN DANA DESA TAHUN 2022 DI DESA NANGA BIANG KECAMATAN KAPUAS KABUPATEN SANGGAU - Susi Krisjuyani; Deky Kurniawan (FOKUS : Publikasi Ilmiah untuk Mahasiswa, Staf Pengajar dan Alumni Universitas Kapuas Sintang., 2025)
The management of Village Funds is an essential element in achieving independent, participatory, and sustainable rural development. Proper Village Fund management can directly improve community welfare and promote equitable development in rural areas. However, in practice, various challenges still hinder the effectiveness of program implementation. In Nanga Biang Village, the implementation of Village Fund management in 2022 was not yet fully optimal. This was caused by several factors, including low community participation, weak supervision of activity implementation, limited capacity of village officials, and suboptimal financial administration. Based on these conditions, the researcher conducted this study with the research question: How was the implementation of Village Fund management in 2022 in Nanga Biang Village, Kapuas District, Sanggau Regency? The purpose of this study is to describe the implementation of Village Fund management in 2022 in a systematic, factual, and accurate manner. The study uses a qualitative descriptive method, with informants including the Village Head, Village Secretary, Chair of the Village Consultative Body (BPD), and community beneficiaries. The results show that the implementation of the Village Fund in Nanga Biang Village generally followed existing procedures. However, some shortcomings remain, particularly in terms of transparency, the effectiveness of development and empowerment activities, and the need to strengthen the technical and managerial capacity of village officials. Additionally, the implementation has not been entirely based on actual community needs due to limited community involvement in the process.